1987
DOI: 10.1016/s0735-1097(87)80122-5
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular infarction: Frequency, size and topography in coronary heart disease: A prospective study comprising 107 consecutive autopsies from a coronary care unit

Abstract: During a 14 month period autopsies were performed on 107 patients with coronary heart disease and the results were evaluated prospectively with special reference to right ventricular infarction. A total of 214 regional infarcts were found, 107 (50%) of which involved the right ventricle. Right ventricular infarction was found in 90 hearts (84%), but only three isolated right ventricular infarcts were seen. Right ventricular involvement was found with equal frequency in anterior and posterior infarction (64 ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0
12

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(124 citation statements)
references
References 25 publications
6
98
0
12
Order By: Relevance
“…Поэтому у больных ИБС можно ожидать выявления связи дилатации ПЖ с множественными коронарными стенозами или с бόльшим размером асинергии ЛЖ. ИМ ПЖ чаще развивается в ре-зультате поражения проксимального отдела недоминиру-ющей правой КА [10,11], поэтому дилатация ПЖ у наших пациентов могла быть связана с поражением этой локали-зации при левом типе коронарного кровообращения. Од-нако по типу коронарного кровообращения, распростра-ненности или локализации поражений КА и индекса аси-нергии ЛЖ межгрупповых различий не выявлено.…”
Section: Discussionunclassified
“…Поэтому у больных ИБС можно ожидать выявления связи дилатации ПЖ с множественными коронарными стенозами или с бόльшим размером асинергии ЛЖ. ИМ ПЖ чаще развивается в ре-зультате поражения проксимального отдела недоминиру-ющей правой КА [10,11], поэтому дилатация ПЖ у наших пациентов могла быть связана с поражением этой локали-зации при левом типе коронарного кровообращения. Од-нако по типу коронарного кровообращения, распростра-ненности или локализации поражений КА и индекса аси-нергии ЛЖ межгрупповых различий не выявлено.…”
Section: Discussionunclassified
“…More details about the data can be found at the RVSC website. 2 Ground truth manual segmentations were provided only for the training set. For testing data sets, initial manual contours were drawn using a programme developed in-house that uses spline smoothing, and therefore, require a small number of points to be provided by the user.…”
Section: Rv Segmentation Challenge Datamentioning
confidence: 99%
“…Although clinically evidenced with several studies [2,3], the importance of RV analysis was overlooked in the last decade. Andersen et al [2] showed that up to 50% of all regional infarcts are RV related.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dessa forma, a oclusão da artéria coronária direita antes de seus ramos leva à isquemia do ventrículo direito 364 . O infarto do ventrículo direito hemodinamicamente significante ocorre quase exclusivamente na presença de infarto inferior 365 . Pelo fato de o ventrículo direito ter massa muscular muito menor que o ventrículo esquerdo (principalmente pela menor resistência vascular do circuito pulmonar), sua demanda de oxigênio …”
Section: -Considerações Anatômicas E Fisiopatológicasunclassified